Processing of Customized Automotive Components Nickel Aluminium Bronze Material using Metal Casting Techniques - Rashidi, M. M. (Faculty of Mechanical & Automotive Engineering Technology, 2021)
Most rotating components for automotive and industrial usage utilize metal due to the material flexibility and ductility in order to ensure failure part gives early warning or indication. So, a failure can be forecasted by stressstrain condition without the disaster of sudden failure. Nickel Aluminium Bronze (NAB) alloy is capable to offer such ductility during operation and gives a signal prior to material failure.